THE CHALLENGES OF ENFORCEMENT OF EU COMMON VALUES - Limantė, Agnė (Teisė, 2016)
The article analyses the means of protection of the key EU values embedded in Article 2 of the Treaty of the European Union (TEU). The paper claims that the mechanisms designed for protection of EU values are rather weak and are suffering from political unwillingness of EU Member States to act against other EU states. Due to the limits of Articles 258–260 of the TFEU (providing for infringement procedure), protection of EU values is relying solemnly on a special political procedure, established by the Article 7 TEU. This procedure is often considered as the measure of last resort or even ‘nuclear option’ and has never been applied because of high thresholds needed for activating it and for being considered as politicaly counterproductive.The two initiatives suggested by the Commission and the Council in 2014 should be considered as additional, though a tiny steps towards enhanced protection of EU values in general, and the rule of law in particular. Nevertheless, the ‘ideal’ solution is still not on the table as both, the Commission’s and the Council’s proposals do not appear adequate to tackle the problem of reversing ‘anti-rule of law’ tendencies. The author investigates and compares the present proposals and considers whether they are proper instruments for addressing fundamental challenges EU face. The paper suggests, that ‘pre-Article 7’ procedure put forward by the Commission is prefarable (in terms of effectiveness) to the Council’s proposal of annual rule of law dialogue.